Med pragmatizmom in grožnjami – FLRJ 1950–1951 - Čelig, Tomaž (Studia Historica Slovenica, 2024)
The article examines the period between 1950 and 1951, when the Federal People's Republic of Yugoslavia (sln. Federativna ljudska republika Jugoslavija – FLRJ), following its split with the Informbiro, faced serious economic and political challenges. During this time, under Soviet pressure and an economic blockade, the FLRJ sought assistance from the West, which proved crucial for its survival and the normalization of the country's situation. Particular emphasis is placed on the impact of a devastating drought that further worsened the already critical economic state and on Western aid, which was essential for stabilization. The article also analyses how these events influenced changes in the FLRJ's foreign policy and its relations with both the East and the West. In preparing the article, the authors thoroughly examined relevant literature, archival sources, and newspapers, ensuring the accuracy of the content and providing a comprehensive insight into the events of that period.
Keywords: diplomacija; Federal People's Republic of Yugoslavia; FLRJ; foreign policy; history of Yugoslavia; informbiro; Soviet Union; Sovjetska zveza; USA; ZDA; zgodovina Jugoslavije; zunanja politika